2010
DOI: 10.1143/jjap.49.082702
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Lasing Action of Nd3+- and Cr3+-Doped Yttrium Aluminum Garnet Ceramics Based on Phonon-Assisted Cross-Relaxation Using Solar Light Source

Abstract: We constructed a theory to explain the mechanism of laser generation with a high optical–optical conversion efficiency for Nd3+- and Cr3+-doped yttrium aluminum ceramics when sunlight or lamplight sources are used for pumping. As a result, a unique mechanism of laser action was found where the solar or lamp-light power could be converted to laser power with a high efficiency close to 80%, which has not previously been observed. The high conversion efficiency was not only considered to be based on one-to-one ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
(50 reference statements)
0
25
0
Order By: Relevance
“…12 A remarkable increase in laser gain and output laser power have already been observed. 12 Previously, some reports on the measurement of the fluorescence lifetime of the Nd/Cr:YAG ceramics excited with narrow-band light were published. 1À14 However, an increase in fluorescence lifetime was not observed as a function of temperature.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…12 A remarkable increase in laser gain and output laser power have already been observed. 12 Previously, some reports on the measurement of the fluorescence lifetime of the Nd/Cr:YAG ceramics excited with narrow-band light were published. 1À14 However, an increase in fluorescence lifetime was not observed as a function of temperature.…”
Section: Introductionmentioning
confidence: 90%
“…10 As a result of the analysis, we found that the integrated spectral intensity of the fluorescence components from T 2 level to 4 T 1 level occurs efficiently due to multi-phonon relaxation. 10,12,13 The first process is indicated in Fig. 7, which is independent of the temperature of the laser medium.…”
Section: Fluorescence Lifetime Of Nd Ionsmentioning
confidence: 97%
See 2 more Smart Citations
“…Cr,Nd:YAG is one of the most investigated media [11], and the transparent YAG ceramic is mainly used in recent studies [12]. However, absorption of Cr,Nd:YAG around 500 nm which corresponds to the wavelength of solar radiation peak and the absorption cross section are relatively small even at the absorption peak wavelength.…”
Section: Introductionmentioning
confidence: 99%